An ultra-high ion selective hybrid proton exchange membrane incorporated with zwitterion-decorated graphene oxide for vanadium redox flow batteries. Issue 20 (8th May 2019) - Zhang, Yuxia; Wang, Haixia; Liu, Bo; Shi, Jingli; Zhang, Jun; Shi, Haifeng
Abstract : A good trade-off effect between proton conductivity and vanadium ion permeability contributing ultra-high ion selectivity is demonstrated for SPEEK/ZC-GO hybrid membranes influenced by zwitterionic ZC-GO nanofillers. Abstract : An ultra-high ion-selective hybrid membrane (SPEEK/ZC-GO) composed of sulfonated poly(ether ether ketone) (SPEEK) and zwitterion-decorated graphene oxide (ZC-GO) containing ammonium and sulfonic acid groups is designed and prepared for all vanadium redox flow batteries (VRFBs). SPEEK/ZC-GO hybrid membranes exhibit higher proton conductivity and lower vanadium ion permeability than pristine SPEEK and Nafion 117 membranes. The good trade-off effect between proton conductivity and vanadium ion permeability offers ultra-high ion selectivity to SPEEK/ZC-GO hybrid membranes, and the SPEEK/ZC-GO-2 hybrid membrane gives the highest ion selectivity, 26.0 × 10 3 S min cm −3, which is about 6.5 and 6.0-fold higher than Nafion 117 (4.0 × 10 3 S min cm −3 ) and pristine SPEEK membranes (4.3 × 10 3 S min cm −3 ), respectively. The VRFB with the SPEEK/ZC-GO-2 hybrid membrane exhibits a significantly slower self-discharge rate, retaining an open circuit voltage of 1.3 V for 132 h, than Nafion 117 (23.5 h) and pristine SPEEK membranes (38 h). The SPEEK/ZC-GO-2 hybrid membrane demonstrates higher coulombic efficiencies (CE: 98.5–99.2%) and energy efficiencies (EE: 91.4–83.9%) at 50–100 mA cm −2, as compared with Nafion 117 (CE: 94.0–97.1%, EE: 83.5–74.7%) and pristine SPEEK membranes (CE: 94.5–97.6%, EE: 82.1–74.4%). Stable cycling performance over more than 200 cycles proves the high chemical stability of the SPEEK/ZC-GO-2 hybrid membrane during long-term operation. This investigation indicates that the SPEEK/ZC-GO hybrid membrane is a promising proton exchange membrane for VRFB systems through controlling the desirable ultra-high ion selectivity.